Designing an incubator of public spaces platform: Applying cybernetic principles to the co-creation of spaces. (August 2022) - Karadimitriou, Nikos; Magnani, Giacomo; Timmerman, Richard; Marshall, Stephen; Hudson-Smith, Andy
Abstract: The paper is based on the experience of creating and piloting a functioning 'Incubator' crowdsourcing platform for designing public spaces in an estate regeneration project in South London. The paper uses a cybernetics framework to analyse and present the way the platform itself was created and how issues of effectiveness, efficiency and equity were dealt with. It explores the generic qualities of interface and reviews applications of variety reduction in established crowdsourcing CS) models. It briefly presents the legal and socio-spatial parameters (like property rights) associated with the creation of the Incubators platform as well as the generic rules applicable to human-spatial relationships, based on studies exploring human-spatial interactions. Practical constraints including costs, catchments, life-span and meaningful feedback are looked into, followed by a discussion on social and political limitations associated with this form of public participation. The paper explains how those constraints where taken into account when establishing the operational parameters of the software platform and the experiences gained from the operation of the platform. Challenges and complications, such as the exclusion of actors, are identified together with the responses encountered in practice. While the Incubators platform succeeded in attracting younger planning participation demographics, older demographics were marginalised by the platform's graphical user interface and social networking features. These findings highlight why, in spite of what it promises, 'crowdsourced urbanism' is prone to similar traits with those of analogue participation. In that sense, creating a CS platform which could convey the grass-roots ideas of actors and users of urban spaces in an efficient way that could be applied to a broad range of planning systems, appears to be a challenge. Highlights: A crowdsourcing platform could structurally marginalise older, poor and less IT-skilled people. Efforts to increase inclusiveness could negate the cost and time efficiencies of crowdsourcing. Mainstreaming crowdsourcing would require digital credentials issued to the entire population. There is a trade-off between CS process manageability and the quality of design outcomes.